Pengikatan Diri dalam Mursyid Institusi Keagamaan Pendekatan Konseling Kognisi - Sugandi Miharja (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
This study aims to explore the method of the murshidan guidance system for congregations. There is a rare phenomenon where activities in a mosque do not stop and continue to be visited by worshipers from various walks of life and regions. This underlies the research question of how the congregational guidance system is in a murshidan manner and what is the attraction of Muslims participating in congregational prayers in the five daily prayers. This mosque became a research location in Citaman Village, Bandung West Java. Data collection techniques used are observation, documentation, and interviews. The study results showed that several methods were applied in the mosque. First, there is the development of Muslims in the community, which is the target area of the mosque. Second, the Jami Mosque holds activities connected for 24 hours by voluntary mosque activists. Third, mosque activists spread the kemurshidan system by having taklim fadhilah amal after every obligatory prayer. Fourth, every week, delegates from residents come to deliberation meetings at the sub-district and Bandung Raya levels. Apart from that, periodically, there are congregations from other areas outside the province, even abroad, who come to the village mosque. The method applied by this mosque is also referred to as the Jamaah Tablighi concept.